Low-Complexity User Scheduling with Switched Tilting for 3D Cellular Systems. (6th April 2015) - Liu, Haijing; Gao, Hui; Lv, Tiejun
Abstract : We propose a low-complexity user scheduling scheme to enhance the sum rate performance for a multicell downlink system, in which the base station (BS) is equipped with a large-scale active antenna array. First, we divide each cell intoN regions according to the vertical beamwidth of the BS antennas. Next, candidate user equipment (UE) items are assigned to corresponding groups to their locations. Each scheduling slot is also divided intoN equal-time subslots. Then, at each subslot, we focus on one UE group, select the optimal number, K *, of UEs for simultaneous data transmission in the manner of round-robin scheduling, and adjust the BS antenna tilting to the optimal angleθ t i l t * . In particular, K * andθ t i l t * for each UE group are both obtained by means of large-system asymptotic analysis. Benefiting from the random matrix theory tools, the asymptotic analytical results are independent of instantaneous channel state information of UE, which make it possible to solveK * andθ t i l t * offline, therefore saving the online computational resources significantly. Numerical results verify that the proposed scheme achieves good sum rate performance with extremely low computational complexity.